Pengaruh karakteristik perusahaan terhadap struktur modal (studi empiris pada perusahaan automotive and allied product yang terdaftar di bursa efek indonesia periode 2008-2011) - Rizal, Prihet Hayezca; Nasir, Azwir; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study was to examine the effect of firm characteristics on capital structure. Its population is automotive and allied products companies listed in Indonesia Stock Exchange the period of 2008-2011. Obtained by using purposive sampling as many as 16 companies in the sample.Independent variables in this study consists of the assets structure, asset growth, profitability, firm size, and managerial ownership, the dependent variable is capital structure. The method of analysis used in this study is multiple linear regression.These results indicate that the asset growth and profitability t count 4,714 to 2,446 t count affect the capital structure, because t table 2,002. While the structure assets with tcount -0.245, t count for firm size and managerial ownership to -0.054 and 1.703 t count no effect on the capital structure because t table 2,002. Adjusted R square value is equal to 0.381, which means 38.1% of the independent variable in this study is able to influence the dependent variable, while the remaining 61.9% is explained by other variables not included in this study, as: business risk, sales stability,etc.Keywords: Assets structure, asset growth, profitability, firm size, managerial ownership and capital structure.